Report of the High-level Policy Dialogue on the Creative Economy for Development (UN New YorkUS, 2012)
Presents the report on the dialogue held to further support governments to enhance their creative economies, as a feasible development option for advancing socio-economic growth, trade and innovation. Reports on the discussions centred on policy strategies, multilateral processes and national experiences, as well as concrete initiatives to foster their creative economies.
Keywords: CREATIVITY